2021
DOI: 10.1177/20587384211059677
|View full text |Cite
|
Sign up to set email alerts
|

Oral booster probiotic bifidobacteria in SARS-COV-2 patients

Abstract: Oral booster-single strain probiotic bifidobacteria could be a potential strategy for SARS-CoV-2. This study aims to evaluate the role of oral probiotic Bifidobacterium on moderate/severe SARS-CoV-2 inpatients. In this single-center study, we analyzed data of 44 moderate/severe inpatients with diagnosed COVID-19 in Istanbul Maltepe University Medical Faculty Hospital, 2020 from 1 November 2020 to 15 December 2020. Clinical and medication features were compared and analyzed between patients with or without prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 22 publications
(32 reference statements)
1
35
0
Order By: Relevance
“…Apart from the conventional risk factors which increase the risk of readmission, interestingly, the rate of readmission increases significantly in patients with dysbiotic gastrointestinal symptoms, according to a gastrointestinal study in Istanbul ( 32 ). Also, the study found that intestinal microbiota affects disease morbidity and mortality ( 33 ). In particular, the Th17/II17-116 immune cascade is responsible for COVID-19 pathology and can increase the severity of the disease ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the conventional risk factors which increase the risk of readmission, interestingly, the rate of readmission increases significantly in patients with dysbiotic gastrointestinal symptoms, according to a gastrointestinal study in Istanbul ( 32 ). Also, the study found that intestinal microbiota affects disease morbidity and mortality ( 33 ). In particular, the Th17/II17-116 immune cascade is responsible for COVID-19 pathology and can increase the severity of the disease ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some articles also evaluated the effect of probiotics on COVID-19 infection. The majority of the studies found the probiotics bene cial for COVID-19 patients' recovery [23,[30][31][32][33][34][35][36][37][38][39][40][41]. One study evaluated the positive e cacy of FMT (Fecal microbial transplantation) for COVID-induced GI upset [35].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported the bene cial effects of Bi dobacterium in decreasing mortality rates and hospital admission duration of moderate/severe COVID-19 patients, increasing blood antibody levels, and lowering in ammatory cytokines [31,41]. Similarly, one study reported that the use of Probiotics was associated with a shorter duration of COVID-19 illness and hospitalization and improved the conditions of COVID-19 patients [40].…”
Section: Probiotic Implementationmentioning
confidence: 99%
“…A review of a total of 33 clinical trials related to viral respiratory infections found that beneficial bacteria from probiotic treatment also induced mucosal regeneration and intestinal mucins binding to viruses, lowered viral adhesion to epithelial cells and viral replication, and reduced the risk or duration of respiratory tract infection ( Lehtoranta et al, 2014 ). In another study, among COVID-19 patients who received oral Bifidobacteria treatment, the interleukin-6 levels decreased and the mortality rate was decreased to 5% (from as 25%) ( Bozkurt and Bilen, 2021 ). This approach should be further explored for treatment of hospitalized patients with moderate/severe COVID-19.…”
Section: Probiotics and Covid-19mentioning
confidence: 99%